2019
DOI: 10.1002/app.47674
|View full text |Cite
|
Sign up to set email alerts
|

Creep performance of CNT reinforced glass fiber/epoxy composites: Roles of temperature and stress

Abstract: Carbon nanotubes (CNTs) have been emerged as a potential nanofiller to reinforce polymeric materials to improve their mechanical properties, like strength and modulus. However, time‐dependent deformation of such materials under a constant load and elevated temperature is a matter of concern for long‐term durability of these materials. The present article primarily demonstrates the effects of creep temperature and stress on the reinforcement efficiency of CNT in a glass fiber/epoxy (GE) composite. Two types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 74 publications
(68 reference statements)
1
13
0
Order By: Relevance
“…% of HN, the results were the same after hydrothermal aging in water It can be also noted that the growth of glass transition temperature of the epoxy upon hydrothermal aging associated to post-curing and decrease of the free volume correlated well with the increase of elastic modulus (see Figures 7a and 8a). For the case of the epoxy filled with CNT, CNF, or HN, there was minimal effect on the glass transition temperature before/after hydrothermal aging and this result agrees well with the literature data being attributed to several opposite factors, such as formation of interphase/interface and agglomeration of the nanoparticles, as well as differences in the crystallinity and the crosslink density of the epoxy resin and the PNC [6,11,28].…”
Section: Discussionsupporting
confidence: 88%
“…% of HN, the results were the same after hydrothermal aging in water It can be also noted that the growth of glass transition temperature of the epoxy upon hydrothermal aging associated to post-curing and decrease of the free volume correlated well with the increase of elastic modulus (see Figures 7a and 8a). For the case of the epoxy filled with CNT, CNF, or HN, there was minimal effect on the glass transition temperature before/after hydrothermal aging and this result agrees well with the literature data being attributed to several opposite factors, such as formation of interphase/interface and agglomeration of the nanoparticles, as well as differences in the crystallinity and the crosslink density of the epoxy resin and the PNC [6,11,28].…”
Section: Discussionsupporting
confidence: 88%
“…Similar results of T g increasing after moisture absorption were attributed to the post-curing phenomenon during physical ageing for a partially cured system [5]. The minimal effect of the addition of both N and SA on the glass transition temperature is fully in line with available literature and it can be attributed to several contrasting factors such as the existence of interphases/interfaces on the surface of the nanoparticles, agglomerates, changes in crystallinity, and the crosslinking density of the epoxy resin [7,33].…”
Section: Resultsmentioning
confidence: 71%
“…Figure 10 compares the strain rate data computed using the BM and FPLM for the creep tests under pure hoop tensile loading and pure axial compression. A phase of decreasing strain rate is initially observed which corresponds to the primary creep stage [ 42 ]. It is further shown that the pure hoop tensile tests, having a higher applied stress of 10 MPa, resulted in higher strain rates than the axial compression tests, which had a stress level of 5 MPa.…”
Section: Resultsmentioning
confidence: 99%